Kajian Kelayakan Usahatani Kopi Organik dan Anorganik berdasarkan Aspek Finansial di Desa Kayumas Kabupaten Situbondo, Indonesia - Fitriyaningsih Fitriyaningsih; Abdullah Muhlis (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Coffee is a strategic plantation commodity that plays an important role as a source of income for farmers and a contributor to foreign exchange. The national coffee demand, which increases by 8% per year, is not offset by a decrease in production from 771 thousand tons (2022) to 756.1 thousand tons (2023), due to climate change, pest attacks, and a lack of plant rejuvenation. The global trend towards organic and specialty coffee opens up opportunities for sustainable agribusiness development. This study aims to analyze the feasibility of organic and inorganic coffee farming purposively in Kayumas Village, Situbondo Regency, with 60 respondents selected through quota sampling from two farmer groups. Data were obtained from secondary sources and analyzed using investment criteria: NPV, Net B/C, IRR, and PP. The results of the analysis show that: (1) the NPV of organic and inorganic farming is positive at Rp13,125,667/ha and Rp6,493,270/ha at an interest rate of 6%; (2) the Net B/C value is 2.02 and 1.59, respectively; (3) The IRR is higher than the interest rate, namely 22.06% and 38.06%; and (4) the Payback Period of both farming systems is faster than their economic life, namely an average of 2 years. Organic coffee farming offers higher profitability and greater feasibility than inorganic farming, making it more promising for development amid the increasing demand for organic coffee and the need for sustainable agribusiness. These findings provide a basis for farmers and policymakers in making decisions about developing efficient, sustainability-oriented coffee farming businesses.